Anti-Cancer Activity of Maize Bioactive Peptides - Díaz-Gómez, Jorge L.; Castorena-Torres, Fabiola; Preciado-Ortiz, Ricardo E.; García-Lara, Silverio (Frontiers in Chemistry, 2017)
Cancer is one of the main chronic degenerative diseases worldwide. In recent years, consumption of whole-grain cereals and their derived food products has been associated with reduction risks of various types of cancer. Cereals main biomolecules includes proteins, peptides, and amino acids present in different quantities within the grain. The nutraceutical properties associated with peptides exerts biological functions that promote health and prevent this disease. In this review, we report the current status and advances on maize peptides regarding bioactive properties that have been reported such as antioxidant, antihypertensive, hepatoprotective, and anti-tumour activities. We also highlighted its biological potential through which maize bioactive peptides exert anti-cancer activity. Finally, we analyse and emphasize the possible areas of application for maize peptides.